(untitled) (Research, Society and Development, 2020)
The consumption of goji berry (Lycium barbarum L.) has aroused worldwide interest due to its excellent nutritional and functional properties, related to the reduced risk of developing chronic diseases due to oxidative stress, being classified as a “super food”. Thus, the aim of this study was to evaluate the effects of aqueous extract of goji berry on hematological and biochemical parameters in Wistar rats treated with warfarin. The concentration of total phenols was determined by the Folin-Ciocalteau reagent, while the antioxidant capacity determined by the DPPH test. The animals were divided into four experimental groups: distilled water (vehicle - negative control); fed daily with the extract (0.18 g.Kg-1); treated daily with water and warfarin (0.5 mg.Kg-1 - positive control) and those treated concomitantly with the extract and warfarin, for seven days. Our results showed a high amount of polyphenols (6.19 ± 0.3 mg EAG.g-1) in the 10 % aqueous extract (m.v-1) and suggests considerable antioxidant activity (IC50 1068 µg.mL-1). We did not observe significant differences between the biochemical and hematological profiles, or even signs of toxicity of the extract when administered alone. The data from concomitant use with warfarin are impressive and show a significant increase in prothrombin time, with the potential for bleeding. Collectively, these observations suggest the propensity for a clinically important interaction between warfarin and Lycium barbarum L., which compromises the safety of this drug and sheds light on future research related to a deeper understanding of the molecular mechanisms involved.